Efek Hipoglikemik Infus Kulit Kacang Tanah (Arachis Hypogaea L) PadaTikus Putih Jantan (Wistar) Yang Dibebani Glukosa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT People in some parts of Yogyakarta use peanut pericarpium as alternative medicine for diabetes mellitus (DM). This research was conducted to examine hypoglycemic activity of peanut pericarpium infusion on rat. Wistar male rats were loaded by glucose solution at dose 2 g/kg body weight (BW), then they were administered orally by peanut pericarpium infusion at doses 1.5